Development and Validation of UPLC-PDA and UV Methods for the Quantitative Estimation of Ascorbic Acid (ASAC) in Pharmaceutical Formulations - Ahmad, Wasim; Banu, Nuzhat; Ahmad, Ayaz; Hassan, Yousif Amin; Surour, Manal; Aleid, Rawan Rashad; Patel, Munfis Samir; Lewis, Sharell; Ashraf, Kamran (Indian Journal of Pharmaceutical Education and Research)
Background: Vitamin C, also called Ascorbic Acid (ASAC), is a potent antioxidant that has a significant role in fighting infections and helps in healing wounds. Aim: Quantitative estimation of ASAC in formulations is of significance in quality control. A simple, sensitive, highly efficient and reliable Ultra-Performance Liquid Chromatography (UPLC) analytical method was suggested for evaluating ASAC in various pharmaceutical products (chewable tablet, effervescent tablets, and capsules). Materials and Methods: The UPLC method was developed on a C8 column, and the column oven temperature was adjusted to 35±5ºC using Empower software. The mobile phase used was water, methanol, and 0.1% formic acid (16:80:04, v/v/v). 1 μL volume was injected on isocratic elution with a flow rate of 0.3 mL/min, and 2 min run time for the separation of ASAC. The peak absorbance of ASAC was noted at 244.3 nm. Results: The linearity of the ASAC calibration curve in the range of 25-125 ng/mL and 1-100 μg/mL for the developed UPLC and UV methods, respectively. The values of the correlation coefficient (R2) for ASAC were assessed to be 0.9987 and 0.9873 by UPLC and UV methods, respectively. The results obtained showed a strong correlation between ASAC concentration and UPLC and UV response. Conclusion: The proposed suggested method demonstrated linearity, precision, accuracy, specificity, and robustness, for the quantitative assessment of pharmaceutical formulations consisting of ASAC within a short period of time.
Keywords: UPLC; UV spectrophotometer; TLC; Vitamin C; Marketed formulation.